2016
DOI: 10.1007/s10803-016-2852-z
|View full text |Cite
|
Sign up to set email alerts
|

Intolerance of Uncertainty Predicts Anxiety Outcomes Following CBT in Youth with ASD

Abstract: Modified cognitive-behavioral therapy (MCBT) has been demonstrated to reduce anxiety in youth with autism spectrum disorder (ASD). However, non-response rates are fairly high. Few studies have investigated factors associated with response. Intolerance of uncertainty (IU) is a treatment target for anxiety and worry in neurotypical populations and has been linked to anxiety and ASD. We sought to examine whether IU affects outcomes following MCBT in 43 children, ages 8-14 years, with ASD without intellectual disa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 46 publications
3
52
0
Order By: Relevance
“…A parallel parent‐report version of the IU Scale (IUS‐P), which reports on children's experiences, was also administered. The modified IUS scales had good to excellent internal consistency in a sample of children with ASD and co‐occurring anxiety disorders [IUS‐P α = 0.96, IUS‐C α = 0.89; Keefer et al, ]. Internal consistency for the modified IUS child and parent was found to be good to excellent in the present study (α's = .84, .95, respectively).…”
Section: Methodssupporting
confidence: 51%
See 1 more Smart Citation
“…A parallel parent‐report version of the IU Scale (IUS‐P), which reports on children's experiences, was also administered. The modified IUS scales had good to excellent internal consistency in a sample of children with ASD and co‐occurring anxiety disorders [IUS‐P α = 0.96, IUS‐C α = 0.89; Keefer et al, ]. Internal consistency for the modified IUS child and parent was found to be good to excellent in the present study (α's = .84, .95, respectively).…”
Section: Methodssupporting
confidence: 51%
“…The IUS is not validated in youth with ASD. Current and prior data, however, show acceptable internal consistency of the modified measure [Keefer et al, 2016], and the IUS-P has been utilized in multiple studies of youth with ASD [Boulter et al, 2014;Chamberlain et al, 2013;Neil et al, 2016]. The SCARED has been used in prior studies of children with ASD [e.g., Blakeley-Smith, Reaven, Ridge, & Hepburn, 2012;Lohr et al, 2017;Stern, Gadgil, Blakeley-Smith, Reaven, & Hepburn, 2014]; however, there are concerns about children's' ability to selfreport and the specificity of anxiety screening measures with this population [Kerns et al, 2015].…”
Section: Discussionmentioning
confidence: 99%
“…The parents easily differentiated IU from a general dislike of change, including discomfort with unknown situations such as delayed flights on a planned trip; and discomfort with uncertainty even in known situations, when a child moves to middle school and is required to use a pen instead of a pencil but is afraid she might make a mistake and not be able to erase it. Keefer et al (2016) reported that ASD children completing the Face Your Fears cognitive behavioral therapy (CBT) protocol had significantly reduced parent-reported anxiety symptoms. Importantly, pre-treatment IU scores significantly mediated the change in anxiety scores such that children with higher pre-treatment IU showed less improvement of their anxiety symptoms.…”
Section: Intolerance Of Uncertainty In Asdmentioning
confidence: 99%
“…Rapidly emerging data suggests that standard behavioral and pharmacological mental health interventions will benefit from understanding and targeting highly-specific underlying mechanisms (Keefer et al, 2016; Walsh et al, 2016). For example, interventions directed at improving sensory integration could potentially reduce anxiety in ASD, although little research in this area has been done to date (Watts et al, 2016).…”
Section: Implications For Treatmentmentioning
confidence: 99%
See 1 more Smart Citation